Hydrodynamic growth experiments with the 3-D, "native-roughness" modulations on NIF. (May 2016) - Smalyuk, V A; Weber, S V; Casey, D; Clark, D S; Coppari, F; Field, J E; Haan, S W; Hammel, B A; Hamza, A; Hsing, W; Landen, O; Nikroo, A; et al.
Abstract: Hydrodynamic instability growth experiments with threedimensional (3-D) surface-roughness modulations were performed on plastic (CH) shell spherical implosions at the National Ignition Facility (NIF). The initial capsule outer-surface roughness was similar to the standard specifications ("native roughness") used in a majority of implosions on NIF. At a convergence ratio of ∼3, the measured tent modulations were close to those predicted by 3-D simulations (within ∼15-20%), while measured 3-D, broadband modulations were ∼3-4 times larger than those simulated based on the growth of the known imposed initial surface modulations. One of the hypotheses to explain the results is based on the increased instability amplitudes due to modulations of the oxygen content in the bulk of the capsule. These new experiments results have prompted looking for ways to reduce UV light exposure during target fabrication.